Model Konflik Kognitif Konseptual Berbasis Visualisasi Dinamis (Model KKVD) untuk Meningkatkan Pemahaman Konseptual Transformasi Geometri - Firdaus Adji Saputro; Ibrahim Sani Ali Manggala; Rosmaiyadi; Anwas Mashuri; Mohammad Nurwahid (FKIP Universitas Mataram, 2026)
This study develops and examines the initial effectiveness of the Conceptual Cognitive Conflict Model Based on Dynamic Visualization (KKVD Model) for improving students’ conceptual understanding of geometric transformations. Initial effectiveness is defined here as the model’s capacity to produce statistically and practically significant differences in learning outcomes during a small-scale field trial, prior to broader dissemination. Using a Research and Development (R&D) design adapted from Thiagarajan’s 4D model (limited to the Develop phase), followed by a quasi-experimental field trial, the KKVD Model was validated by three experts (mean score 87.7%, Very Valid). The experimental group (n = 20) and control group (n = 20) consisted of Grade XI students from SMK Widyagama Malang, selected through purposive sampling based on comparable prior achievement and class availability. The experimental group’s mean posttest score (81.46) significantly exceeded the control group (72.29), with N-Gain of 0.70 (high) versus 0.54 (medium), and a large effect size (Cohen’s d = 1.12; p < 0.001). The most substantial improvements occurred in the conceptual relations and generalization dimensions, reflecting deeper conceptual restructuring. The KKVD Model systematically integrates cognitive conflict, GeoGebra-based dynamic visualization, and conceptual reconstruction into a validated instructional syntax, offering a promising alternative for meaningful geometry transformation learning.